A prospective, observational study to explore health disparities in patients with heart failure—ethnicity and financial status. (1st January 2017) - Wu, Jia-Rong; Lennie, Terry A; Moser, Debra K
Abstract: Background: Health disparities are related to race/ethnicity, financial status and poor self-care behaviors, but the relationships between these factors remain unknown. Objective: To explore the relationships between race/ethnicity, financial status and cardiac event-free survival, and the reasons for any disparities in patients with heart failure (HF). Methods: We collected demographic data (e.g., race/ethnicity and financial status), clinical data (e.g., medication regimen) and self-care behaviors (by the Self-Care of Heart Failure Index) in 173 HF patients at baseline. Patients were grouped by race/ethnicity (African–American and Caucasian) and financial status (higher if they reported having "enough or more than enough to make ends meet" and lower if they "did not have enough to make ends meet"). Chi-square tests, t -tests and survival analyses were used to explore the relationships between race/ethnicity, financial status, self-care and survival. Results: African–American race/ethnicity and poor financial status were associated with poor outcomes ( p  < 0.005) when controlling for covariates. HF patients with lower financial status reported engaging in fewer self-care maintenance behaviors than those with higher financial status. African–American HF patients trended to report engaging in fewer self-care maintenance behaviors than Caucasian HF patients. African–Americans with lower financial status had a four- to six-times higher risk of experiencing cardiac events compared to patients who were Caucasian with higher financial status before and after controlling for covariates. Conclusions: African–American HF patients and those with lower financial status had worse outcomes and reported fewer self-care maintenance behaviors. Interventions promoting self-care may decrease the disparity in outcomes and should be tailored to African–Americans and those with lower financial status.